Routines, learning by using and networks: the case of aircraft maintenance - Araujo, Luis (2022)
The purpose of this paper is to explore the notion of routines and its connection to the evolution of “learning-by-using” in a complex network setting, aircraft maintenance. Despite continued theoretical interest, there has been a dearth of empirical studies in how routines emerge and develop in the field. In addition, few studies have considered how routines intersect and interact across conventional organisational boundaries. Aircraft maintenance stands at the junctions of a number of relationships that define and constrain how maintenance operations are to be performed, namely airframe manufacturer-maintenance station and maintenance station-aircraft operator. In addition, aircraft maintenance is governed by a highly formalised set of rules involving formal institutions and regulatory bodies (e.g. industry associations, civil aviation authorities). A system governed by tight routines might be expected to learn only gradually and slowly. The paper discusses how the combination of routines with the accumulation and rapid diffusion of “learning-by-using” mechanisms at different levels of the network of actors directly and indirectly involved in aircraft maintenance